2019
DOI: 10.1142/s0217984919400256
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of flexural strength and compressive strength by heat treatment of PLA filament for 3D-printing

Abstract: Poly-lactic Acid (PLA) is an environmentally friendly material with better stability in heat shrinkage than Acrylonitrile Butadiene Styrene (ABS), such as warping in 3D printing. This study focused on the enhancement of the mechanical properties of PLA filament for 3D printers through different heat treatment temperature and heat exposure time of PLA samples. The results showed that the highest flexural strength was recorded in the PLA sample that went through heat treatment at [Formula: see text] and heat exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Several experiments have been conducted on PLA printed parts, as PLA is one of the most commonly used polymers in FDM. As per Hong et al’s [ 243 ] work, it was noted that the mechanical properties including flexural strength and compressive strength were increased due to heat annealing. The bonds between the layers became much stronger with higher temperatures and longer exposure, whereas a sample treated at 140 °C for 600 s showed the maximum bond between layers.…”
Section: Treatment Methods To Overcome or Minimize The Defects In mentioning
confidence: 75%
See 1 more Smart Citation
“…Several experiments have been conducted on PLA printed parts, as PLA is one of the most commonly used polymers in FDM. As per Hong et al’s [ 243 ] work, it was noted that the mechanical properties including flexural strength and compressive strength were increased due to heat annealing. The bonds between the layers became much stronger with higher temperatures and longer exposure, whereas a sample treated at 140 °C for 600 s showed the maximum bond between layers.…”
Section: Treatment Methods To Overcome or Minimize The Defects In mentioning
confidence: 75%
“…Heat treated specimens increased their layer and raster adhesion. ( a , b , d , e ): [ 243 ], ( c , f ): [ 242 ].…”
Section: Figurementioning
confidence: 99%
“…For the first case, annealing is a postprocessing heat treatment commonly used to improve the mechanical properties and the superficial aspect [12]. Hong et al [13], for example, reported benefits in terms of bending and compressive strength for PLA of around 58.3% and 39.8%, respectively, after heat treatment. In this study, the highest bending strength was obtained at 130 • C for 300 s, while the highest compressive strength was observed at 140 • C for 600 s. In this case, the heat treatment process reduces the debonding zones between the filaments; however, depending on the direction of the external load, the mechanical strength can be affected by slippage of the filaments.…”
Section: Introductionmentioning
confidence: 99%
“…19 According to Hong JH et.al., the heat treatment method decreased the debonding of PLA filaments at high temperatures. 20 According to Wu.W et.al., PEEK samples exhibited greater tensile, bending, and compression strengths than ABS 3D printed samples. 21 Li L et.al., suggested a strength versus porosity formulation that may be applicable for various materials.…”
Section: Introductionmentioning
confidence: 99%